2018
DOI: 10.1111/pce.13402
|View full text |Cite
|
Sign up to set email alerts
|

TRANSPARENT TESTA 4‐mediated flavonoids negatively affect embryonic fatty acid biosynthesis in Arabidopsis

Abstract: Flavonoids are involved in many physiological processes in plants. TRANSPARENT TESTA 4 (TT4) acts at the first step of flavonoid biosynthesis, and the loss of TT4 function causes a lack of flavonoid. Flavonoid deficiency is reportedly the main cause of increased fatty acid content in pale-coloured oilseeds, but details regarding the relationship between seed flavonoids and fatty acid biosynthesis are elusive. In this work, we applied a genetic strategy combined with biochemical and cytological assays to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…The results showed that the expressions of CHI (CSA026735) and DFR (CSA003949) were significantly positive correlation with apigenin O-malonylhexoside, delphinidin 3-O-glucoside, gallocatechin and dihydromyricetin, while the expression of 4CL (CSA007753) was significantly negative correlation with apigenin O-malonylhexoside and delphinidin 3-O-glucoside, suggesting that the exogenous ABA could induce the expressions of genes involved in flavonoid biosynthesis, and hence affected the biosynthesis of flavonoids and derivatives of tea leaves under drought stress.Moreover, previous research showed that inhibition of lipid synthesis redirects the carbon flux into flavonoid metabolism[36]. Recently, CHS-mediated flavonoids were proven to repress embryonic fatty acid biosynthesis in the Arabidopsis seeds, implying a negative correlation between flavonoids and fatty acids biosynthesis in plants[37]. Our results showed that the exogenous ABA drastically decreased the abundances of lipid metabolites and increased the abundances of most flavonoids compared with severe drought.…”
supporting
confidence: 55%
“…The results showed that the expressions of CHI (CSA026735) and DFR (CSA003949) were significantly positive correlation with apigenin O-malonylhexoside, delphinidin 3-O-glucoside, gallocatechin and dihydromyricetin, while the expression of 4CL (CSA007753) was significantly negative correlation with apigenin O-malonylhexoside and delphinidin 3-O-glucoside, suggesting that the exogenous ABA could induce the expressions of genes involved in flavonoid biosynthesis, and hence affected the biosynthesis of flavonoids and derivatives of tea leaves under drought stress.Moreover, previous research showed that inhibition of lipid synthesis redirects the carbon flux into flavonoid metabolism[36]. Recently, CHS-mediated flavonoids were proven to repress embryonic fatty acid biosynthesis in the Arabidopsis seeds, implying a negative correlation between flavonoids and fatty acids biosynthesis in plants[37]. Our results showed that the exogenous ABA drastically decreased the abundances of lipid metabolites and increased the abundances of most flavonoids compared with severe drought.…”
supporting
confidence: 55%
“…2, B, C, E, and F), suggest that melatonin is an important player in the regulatory network that represses the accumulation of both oil and anthocyanins in Arabidopsis seeds. Several previous studies showed a negative correlation between the contents of oil and flavonoids in Arabidopsis seeds (Chen et al, 2012b(Chen et al, , 2014(Chen et al, , 2015Li et al, 2018a;Xuan et al, 2018). Thus, it is generally considered difficult for breeders to synergistically improve both seed oil and flavonoid contents.…”
Section: Discussionmentioning
confidence: 99%
“…FA synthesis is then enhanced at least partially due to increased carbon allocation (Li et al, 2018), as occurs upon deficiency of TT4, the chalcone synthase for flavonoid biogenesis. In the tt4 mutant, WRI1 and its downstream genes involved in glycolysis and FA synthesis are activated, thus driving the reorientated sugar source into the two pathways (Xuan et al, 2018).…”
Section: Signaling Pathwaysmentioning
confidence: 99%